Collaborative school management model for teaching performance in primary-level educational institutions in Cajamarca, 2025 - Alberto, Navarro Soplin, Luis (Edelweiss Applied Science and Technology, 2026)
This study, aligned with Sustainable Development Goal 4 (quality education), aimed to design and validate a collaborative school management model to strengthen teaching performance in public primary-level educational institutions in Cajamarca during 2025. The research followed a quantitative, basic approach, with a non-experimental, cross-sectional design and a descriptive–propositional scope. The population consisted of 603 teachers from public institutions in the province of Jaén, and a sample of 60 teachers was selected through non-probabilistic convenience sampling. Data were collected using a survey technique, applying a 30-item Likert-type questionnaire structured around the dimensions of collaborative school management (leadership, joint work, and planning) and teaching performance (pedagogical performance, lesson execution, and innovation resources). Data analysis was conducted using SPSS v27 through descriptive statistics. The findings revealed predominantly high levels of teaching performance, particularly in pedagogical performance (53.33%), lesson execution (41.67%), and innovation resources (30.00%), although some teachers remained at process and insufficient levels. Based on this diagnostic evidence, a Collaborative School Management Model was developed and validated through expert judgment using a Delphi-type process, achieving high consensus. The study concludes that collaborative management constitutes a viable strategy for improving teaching performance, with significant implications for strengthening institutional practices in similar public educational contexts.